Invasive versus non-invasive management of elderly patients with non-ST elevation myocardial infarction: cohort study based on routine clinical data - Kaura,A; Sterne,J; Trickey,A; Abbott,S; Mulla,A; Glampson,B; Panoulas,V; Davies,J; Woods,K; Omigie,J; Shah,A; Channon,K; et al. (The Lancet, 2020)
BackgroundPrevious trials suggest lower long-term mortality after invasive rather than non-invasive management among patients with non-ST elevation myocardial infarction (NSTEMI), but these excluded very elderly patients.MethodsWe estimated the effect of invasive versus non-invasive management within 3 days of peak troponin on survival in NSTEMI patients aged ≥80 years, using routine clinical data collected during 2010–2017 (NIHR Health Informatics Collaborative). Propensity scores based on pre-treatment variables were derived using logistic regression; patients with high probabilities of non-invasive or invasive management were excluded. Patients who died within 3 days without receiving invasive management were assigned to the invasive or non-invasive management groups based on their propensity scores, to mitigate immortal time bias. We estimated mortality hazard ratios comparing invasive with non-invasive management, and also compared rates of hospital admission for heart failure.FindingsOf 1976 patients with NSTEMI, 101 died within 3 days of their peak troponin, whilst 375 were excluded because of extreme propensity scores. The remaining 1500 patients (56% non-invasive management) had a median age 86 (IQR 82-89) years. During median follow-up of 3.0 (IQR 1.2-4.8) years, there were 613 (41%) deaths. Using inverse probability weighting, adjusted cumulative 5-year mortality was 36% and 55% in the invasive and non-invasive management groups, respectively. The mortality hazard ratio comparing invasive with non-invasive management was 0.64 (95% CI 0.52-0.79) after multivariable adjustment for clinical characteristics and propensity score and inclusion of patients who died within three days. Invasive management was associated with lower incidence of hospital admissions for heart failure (adjusted rate ratio compared with non-invasive management 0.67, 95% CI 0.48–0.93).